THE PRINCIPLE OF PROPORTIONALITY IN THE ISLAMIC INHERITANCE SYSTEM: ASAS PROPORSIONALITAS DALAM SISTEM WARIS ISLAM - Salam, Nor (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2023)
this study is motivated by the debate about the existence of inheritance law in Islam which is often stigmatized as a law that is not friendly to equality between men and women. This background will then be examined in this paper by offering a perspective on the principle of proportionality as the basis of Islamic inheritance law. Through normative-doctrinaire methods of legal studies, this study concludes that the principles of inheritance are eclectic between the principle of proportionality and the principle of justice. This has implications for social propriety that can be between one period of time and another or between one community and another community has different standards. Keywords: Principle of proportionality, Islamic law